2018
DOI: 10.1142/s0219633618400072
|View full text |Cite|
|
Sign up to set email alerts
|

Combining enhanced sampling with experiment-directed simulation of the GYG peptide

Abstract: Experiment directed simulation is a technique to minimally bias molecular dynamics simulations to match experimentally observed results. The method improves accuracy but does not address the sampling problem of molecular dynamics simulations of large systems. This work combines experiment directed simulation with both the parallel-tempering and parallel-tempering well-tempered ensemble replica-exchange methods to enhance sampling of experiment directed simulations. These methods are demonstrated on the GYG tri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…CamShift uses a polynomial expansion of the pair-wise distances between an atom and its neighbors to approximate the NMR chemical shift 40 and thus is differentiable. This has made it a popular choice [41][42][43] and it is implemented in the PLUMED plugin 44 . However, CamShift does not treat side-chains and is insensitive to effects like hydrogen bonding.…”
Section: Introductionmentioning
confidence: 99%
“…CamShift uses a polynomial expansion of the pair-wise distances between an atom and its neighbors to approximate the NMR chemical shift 40 and thus is differentiable. This has made it a popular choice [41][42][43] and it is implemented in the PLUMED plugin 44 . However, CamShift does not treat side-chains and is insensitive to effects like hydrogen bonding.…”
Section: Introductionmentioning
confidence: 99%
“…This peptide density was used to better replicate high peptide concentrations used in NMR experiments (0.5 mM in our experiments). We closely followed the method developed for using EDS with enhanced sampling described in Amirkulova and White …”
Section: Methodsmentioning
confidence: 99%
“…EDS is a type of maximum entropy technique which is used to incorporate experimental data into simulations. It is one of the many recent approaches to minimal biasing simulations to better match experimental data. ,, A recent review of EDS can be found in the work by Amirkulova and White . Given a CV, f ( r⃗ ), EDS computes a potential energy bias U ′( r⃗ , f ( r⃗ )) and adds it to the potential energy of the whole system, U ( r ), such that the ensemble average of f ( r ) matches a chosen value: ⟨ f ( r )⟩ = f̅ .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue, Palmer and coworker discuss hybrid Monte Carlo/molecular dynamics (MC/MD) approach 4 and White and collaborators combine experiment directed simulation with parallel-tempering and parallel-tempering well-tempered ensemble replicaexchange methods. 5 Both methods overcome the limited sampling issues encountered in straightforward molecular dynamics simulations.…”
mentioning
confidence: 99%